Enhancing defect-related photoluminescence by hot implantation into SiO2 layers - Im, S; Jeong, JY; Oh, MS; Kim, HB; Chae, KH; Whang, CN; Song, JH (AMER INST PHYSICS, 1999)
Visible photoluminescence around an orange band of 580 nm wavelength are observed from 300 nm thin SiO2 layers implanted by Si or Ge ions at both substrate temperatures of 25 degrees C [room temperature (RT)] and 400 degrees C (hot). Si implantations at an energy of 30 keV were performed with doses of 5 X 10(15), 3 X 10(16), and 1 X 10(17) cm(-2) while Ge implantations were done at 100 keV with a dose of 5 X 10(15) cm(-2). Samples implanted at 400 degrees C always show much higher intensities of luminescence than those implanted at room temperature. Electron spin resonance signals of the hot-implanted samples indicate relatively smaller amounts of nonradiative defects than those of RT-implanted samples. It is concluded that the hot-implantation effectively enhances the intensity of defect-related photoluminescence by reducing the density of the nonradiative defects and introducing the radiative defects, which contribute to the luminescence in SiO2 layers. (C) 1999 American Institute of Physics. [S0003-6951(99)03507-X].
Keywords: SILICON NANOCRYSTALS; THERMAL SIO2-FILMS; ROOM-TEMPERATURE; LIGHT EMISSION; DIOXIDE; FILMS